Synthesis and Characterization of Monomeric and Dimeric Dihydroxo-Bridged Complexes of Iron(II) with a-Benzilmonoxime - Soleimani, Esmaiel; Ali Naghi Taheri, Sayed (Asian Journal of Chemistry, 2010)
The reaction of a-benzilmonoxime(BMOH) with Fe(CH3COO)2·4H2O in the presence of CH3COONa as a base gives the mononuclear Fe(II) complex, Na[Fe(BMO)3] (1). Treatment of 1 with a methanolic solution of NaOH at room temperature leads to a dinuclear Fe(II)-Fe(II) complex, Na2[Fe(BMO)2OH]2 (2). The complexes were characterized on the basis of their elemental analysis, mass, infrared and electronic spectra. The infrared studies were useful in assigning the coordination mode of the benzilmonoxime ligand to the iron(II) ion. In addition, the presence of a hydroxo-bridge in the dimeric complex 2 is inferred from the infrared spectral studies. The electronic spectra of the complexes revealed two bands due to d-d transitions and one band assignable to an oxygen (pp)®Fe(eg*) LMCT transition observed in both complexes. An additional charge-transfer transition, assignable to μ-hydroxo(pp)®Fe(eg*), was only observed for the dimeric complex 2. The splitting energy (DO) and ligand field stabilization energy are found to be 16825 and -6730 cm-1 for complex 1 and 16200 and -6480 cm-1 for complex 2, respectively.